The Caribbean : Enhancing Economic Integration - Panth, Sanjaya (Departmental Papers; Departmental Paper, 2008)
The Caribbean has made substantial progress in recent years in implementing economic reforms, both at the national and regional level. The Caribbean: Enhancing Economic Integration examines the product of the efforts made by Caribbean policymakers to strengthen regional cooperation and integration, which has yielded economic transformation and tighter integration with the global economy. This volume discusses regional financial integration as a means of deepening financial systems and raising regional growth; the relationship between tax incentives and investment, where harmonized regional action is important in seeking to overcome collective actions problems; and the consequences for the Caribbean of the erosion of trade preferences in key export markets. The book is based on empirical research carried out as part of the IMF's regional surveillance work in the Caribbean.